(3OQGSGJ aj GdeMGSHI GdVQjHjI (B:s (3GdacQ GdeMGSHj ddVQjHI Ydi GdONd (B/s - (3bddj, jMj CMeO eUWais ((3GdEScfOQjI(B: s (3ecJHI GdhaGA GdbGfhfjI(B, s, 2012)
(3jVe eHGOF heaGgje hCSGSjGJ aj GdeMGSHI GdVQjHjI, CSGdjH GdbjGS GdeMGSHj dJMOjO GdONd GdNGVY ddVQjHI ddTNU GdWHjYj hGdEYJHGQj, UhQ ef CSS GdbjGS GdeMGSHj dJMOjO GdONd GdVQjHj Ydi GdfTGW GdJLGQj hGdUfGYj, GdeYGjjQ GdeMGSHjI hGgJeGeGJ GdeMGSHI GdVQjHjIs
(3GdeQGLY U(B.247s
Keywords: (3GdVQGFH(B- (3GdeMGSHIs; (3GdVQjHI Ydi GdONds; (3GdeMGSHI GdVQjHjIs